HYDRATION AND FEEDING ON PRE- AND POST-TRAINING ON AN UNIVERSITARY FEMALE VOLLEYBALL TEAM, RJ. (Fiep Bulletin - online, 2013)
An appropriate feeding during training is essential to volleyball since it supplies body with required substrate for its realization in the form of micro and macronutrients. The goal of this study was to describe the hydration and feeding on periods of pre- and post-training in an universitary female volleyball team from Rio de Janeiro city. In July 2008 it was realized a descriptive, cross-sectional and with primary base study with nine female athletes, aged from 19 to 26 years old, volunteers, all belonging to volleyball female team from UNISUAM. A formulary was developed to make athlete's nutritional follow-up, and it was used by students of nutrition both before and after training. Data were typed, consolidated and analyzed by the software Excel for Windows 2007, as well as explored by means of absolute and relative frequencies and measures of central tendency (mean and standard deviation) from the selected variables. The athletes' average age (years) was 21.9±1.7, the mean height (m) was 1.72±0.05 and the mean body weight were 12.8±4.4Kg and 12.1±3.9Kg, respectively, at pre- and post-training periods. Regarding meal type, it was saw that before training 76.5% of the athletes have a snack and 23.5% have lunch. Among athletes, 69.2% used to hydrate themselves before physical training; 67.3% ingest liquid drinks during training, and 15.7% hydrate themselves after training. The conclusion is that the athletes do not hydrate themselves appropriately before, during and after training.
Keywords: Volleyball; Food Consumption; Hidratation